2011
DOI: 10.3109/00048674.2011.604301
|View full text |Cite
|
Sign up to set email alerts
|

Who Picks Psychiatry? Perceptions, Preferences and Personality of Medical Students

Abstract: Students interested in psychiatry are more likely to be 'open' and view the specialty as interesting and challenging. Such characteristics should be promoted more widely along with countering myths that as a specialty, psychiatry lacks a scientific foundation or is somehow different from mainstream medicine in terms of training and outcomes. Championing psychiatry in this manner may attract more recruits and enhance its prestige.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 33 publications
5
36
2
Order By: Relevance
“…In part 2: The majority of students and intern had a 1366 neutral attitude toward psychiatric knowledge, 62.38%, and 83.28% showed a neutral to negative attitude toward the scientific knowledge of psychiatry, and that most facts in psychiatry are just vague speculations, respectively. These results show that medical students and interns have anegative perception of psychiatry as an unscientific discipline and somehow different from other medical disciplines in term of training and outcome [24], similar results were reported in an Australian study [25]. The emphasis on the biological aspects of psychiatric disorders has been proposed to play a positive role to enhance the attitude toward psychiatry [9,32], as well as the integration of psychiatry into the general hospital settings [33].…”
Section: Positive Attitudesupporting
confidence: 70%
See 2 more Smart Citations
“…In part 2: The majority of students and intern had a 1366 neutral attitude toward psychiatric knowledge, 62.38%, and 83.28% showed a neutral to negative attitude toward the scientific knowledge of psychiatry, and that most facts in psychiatry are just vague speculations, respectively. These results show that medical students and interns have anegative perception of psychiatry as an unscientific discipline and somehow different from other medical disciplines in term of training and outcome [24], similar results were reported in an Australian study [25]. The emphasis on the biological aspects of psychiatric disorders has been proposed to play a positive role to enhance the attitude toward psychiatry [9,32], as well as the integration of psychiatry into the general hospital settings [33].…”
Section: Positive Attitudesupporting
confidence: 70%
“…However, the majority (47.16%) thought that psychiatric treatment had become more efficient in recent years. Two other studies by Melhiet al have reported similar results [25,26]. In part 2: The majority of students and intern had a 1366 neutral attitude toward psychiatric knowledge, 62.38%, and 83.28% showed a neutral to negative attitude toward the scientific knowledge of psychiatry, and that most facts in psychiatry are just vague speculations, respectively.…”
Section: Positive Attitudesupporting
confidence: 67%
See 1 more Smart Citation
“…career choice in psychiatry, or were seriously considering it, was similar to that reported by Malhi et al (2011), but slightly higher than that emerging from Goldacre et al (2013).…”
Section: Discussionsupporting
confidence: 76%
“… career choices (Ackerman & Beier, 2003;Eley, Eley, Bertello, & Rogers-Clark, 2012;Holland, 1997;Jones et al, 2013;Malhi et al, 2011),  career satisfaction (Richardson, Lounsbury, Bhaskar, Gibson, & Drost, 2009)  life satisfaction Josefsson et al, 2011;Magee, Miller, & Heaven, 2013).…”
Section: Temperament and Character Inventory (Tci)mentioning
confidence: 99%